The potential influence of human parainfluenza viruses detected during hospitalization among critically ill patients in Kuwait, 2013–2015. Issue 1 (December 2017) - Essa, Sahar; Al-tawalah, Haya; AlShamali, Sarah; Al-Nakib, Widad
Abstract Background The four types of human parainfluenza viruses (PIV) are important causes of community-acquired pneumonia, particularly in children; however, limited information exists about the incidence of PIV in critically ill patients. The aim of this study is to describe the spectrum, incidence and clinical features of PIV-associated infections diagnosed during the hospital stay of patients admitted to pediatric intensive care unit (PICU) and intensive care unit (ICU) of 5 medical centers across Kuwait. Methods This was a population-based, retrospective study from 2013 to 2015. Specimens were analyzed by molecular methods. This analysis was performed using the database of Virology Unit, Mubarak Al-Kabeer Hospital. Data from 1510 admitted patients with suspected respiratory viral infections was extracted. Results The database contained a total of 39 (2.6%) patients infected with PIV (53.8% male and 46.2% females) and 20 (51.3%) were under 1 year of age. The most frequently isolated type was type 3 (28, 71.8%) followed by type 1 (9, 23.1%). At admission the most common clinical diagnosis was pneumonia in 12 patients (30.8%, p < 0.05) followed by bronchiolitis in 10 patients (25.6%). Conclusion PIV plays an important yet unrecognized role in the outcomes of PIUC and ICU patients. Our results contribute to the limited epidemiologic data of PIV in PIUC and ICU in this region.